Peroxiredoxin 6 Modulates Insulin Secretion and Beta Cell Death via a Mitochondrial Dynamic Network - Pacifici, Francesca; Della-Morte, David; Capuani, Barbara; Coppola, Andrea; Scioli, Maria Giovanna; Donadel, Giulia; Andreadi, Aikaterini; Ciccosanti, Fabiola; Fimia, Gian Maria; Bellia, Alfonso; Orlandi, Augusto; Lauro, Davide (Frontiers in Endocrinology, 2022)
In pancreatic beta cells, mitochondrial metabolism controls glucose-stimulated insulin secretion (GSIS) by ATP production, redox signaling, and calcium (Ca2+) handling. Previously, we demonstrated that knockout mice for peroxiredoxin 6 (Prdx6-/-), an antioxidant enzyme with both peroxidase and phospholipase A2 activity, develop a mild form of diabetes mellitus with a reduction in GSIS and in peripheral insulin sensitivity. However, whether the defect of GSIS present in these mice is directly modulated by Prdx6 is unknown. Therefore, the main goal of the present study was to evaluate if depletion of Prdx6 affects directly GSIS and pancreatic beta β-cell function. Murine pancreatic β-cell line (βTC6) knockdown for Prdx6 (Prdx6KD) was employed, and insulin secretion, ATP, and intracellular Ca2+ content were assessed in response to glucose stimulation. Mitochondrial morphology and function were also evaluated through electron microscopy, and by testing mitochondrial membrane potential, oxygen consumption, and mitochondrial mass. Prdx6KD cells showed a significant reduction in GSIS as confirmed by decrease in both ATP release and Ca2+ influx. GSIS alteration was also demonstrated by a marked impairment of mitochondrial morphology and function. These latest are mainly linked to mitofusin downregulation, which are, in turn, strictly related to mitochondrial homeostasis (by regulating autophagy) and cell fate (by modulating apoptosis). Following a pro-inflammatory stimulus (typical of diabetic subjects), and in agreement with the deregulation of mitofusin steady-state levels, we also observed an enhancement in apoptotic death in Prdx6KD compared to control cells. We analyzed molecular mechanisms leading to apoptosis, and we further demonstrated that Prdx6 suppression activates both intrinsic and extrinsic apoptotic pathways, ultimately leading to caspase 3 and PARP-1 activation. In conclusion, Prdx6 is the first antioxidant enzyme, in pancreatic β-cells, that by controlling mitochondrial homeostasis plays a pivotal role in GSIS modulation.